The Synthesis and Future Directions of Empirical Research on International Students in the United States: The Insights from One Decade - Krsmanovic, Masha (Journal of International Students, 2021)
The purpose of this systematic review was to identify the trends in empirical research on international students in the United States produced between 2010 and 2019. After reviewing and synthesizing the characteristics of 334 research articles published over the past decade, I identify the areas that have been overly researched and the domains that have not yet been adequately explored. The overall findings of this review indicate that recent scholarly efforts have not always been aligned with the international student representation on U.S. campuses. Consequently, I provide eight critical recommendations for future research in the field in the context of over-and underresearched institutional sites (e.g.,institutional type and control), international student populations (e.g.,academic level, field of study, and country of origin), research methods employed, and research questions examined.